Electrochemical and mARC‐Catalyzed Enzymatic Reduction of para‐Substituted Benzamidoximes: Consequences for the Prodrug Concept "Amidoximes instead of Amidines". Issue 2 (15th December 2014) - Bauch, Eva; Reichmann, Debora; Mendel, Ralf‐Rainer; Bittner, Florian; Manke, Anne‐Marie; Kurz, Philipp; Girreser, Ulrich; Havemeyer, Antje; Clement, Bernd
Abstract The mitochondrial amidoxime reducing component (mARC) activates amidoxime prodrugs by reduction to the corresponding amidine drugs. This study analyzes relationships between the chemical structure of the prodrug and its metabolic activation and compares its enzyme‐mediated vs. electrochemical reduction. The enzyme kinetic parameters KM and Vmax for the N‐reduction of ten para‐substituted derivatives of the model compound benzamidoxime were determined by incubation with recombinant proteins and subcellular fractions from pig liver followed by quantification of the metabolites by HPLC. A clear influence of the substituents at position 4 on the chemical properties of the amidoxime function was confirmed by correlation analyses of 1H NMR chemical shifts and the redox potentials of the 4‐substituted benzamidoximes with Hammett's σ. However, no clear relationship between the kinetic parameters for the enzymatic reduction and Hammett's σ or the lipophilicity could be found. It is thus concluded that these properties as well as the redox potential of the amidoxime can be largely ignored during the development of new amidoxime prodrugs, at least regarding prodrug activation.